Possession of land - Wonnacott, Mark (Cambridge University Press, 2006)
Nothing is more important in English land law than 'possession'. It is the foundation of all title, rights and remedies. But what exactly is it, and why does it still matter? This book, first published in 2006, is about the meaning, significance and practical effect of the concept of possession in contemporary land law. It explains the different meanings of possession, the relationship between possession and title, and the ways in which the common law and equity do, and do not, protect possession. The rights and remedies of freeholders, tenants and mortgage lenders, between themselves and against third parties, are all to some extent dependent on questions of status and possession. This book shows how. It is designed to provide an understanding of the basic principles for the student, and answers to difficult, real problems for the practitioner